The electronic auction as an instrument to ensure the principle of efficiency in the brazilian public administration (Research, Society and Development, 2021)
The transformations undergone by the Public Administration over the years have reflected on all administrative activities performed by its agents. Among them, it is worth highlighting those that have occurred in the way public purchases are made, in view of the compliance with the principle of efficiency of the Public Administration. In this context, the Electronic Auction, considered by the diction of Decree No. 10.024/2019 as mandatory for all organs of the federal public administration, is the most modern tool used.  Thus, this theoretical essay aims to characterize the electronic auction, as a tool to ensure administrative efficiency, using the qualitative approach. To this end, in the first half of the year 2021, studies related to the theme were identified, available on electronic platforms of indexed content. Among the results, it was identified that the electronic auction enhances the effectiveness of the principle of efficiency in public administration, due to the speed, transparency and optimization of costs and benefits obtained in the procurement processes. It is worth noting the presence of the inversion of phases in this bidding process, where the proposals are first judged and then the documents of the winning companies are analyzed.